PEMBERDAYAAN MASYARAKAT PESISIR DI KABUPATEN BATANG JAWA TENGAH MELALUI PENGEMBANGAN INDUSTRI GALANGAN KAPAL TRADISIONAL - Trimulyono, Andi; Budi Santosa, Ari Wibawa (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2014)
Batang which is located on the north coast of Central Java with an area of 788.642 km2 area of the position of the district of Batang put the economy on a path north of the island of Java. Coastal region of this district, make there is a potential that can be developed into a valuable asset to the nation i.e the traditional shipbuilders. Karangasem is one of the districts that have the potential for ship production In terms of productivity shipyard,one of traditional shipbuilder is CV. Laksana Abadi as traditional shipyard in year 2000 capable of producing ships totaling 18 units within a period of 12 months. In Batang district not only CV. Laksana Abadi but also CV. Rizki Maulana Bahari engaged in the manufacture of wooden ships that have smaller productivity due to the still relatively new in Karangasem. Because of the traditional manufacturing process, so it can be said to be still very traditional methods that shipbuilder built they ship and also their belief in technology still low itâ€™s can seen from the construction of the ship is still in traditional way. So KKN-PPM is intended to bridge between the use of the latest technology by using ofÂ  fishipro or Delftship software. Based on the mapping problem then formed five clusters, namely cluster Ship Design With Software, Cluster of Shipyard Production, Cluster Marketing Information System, Cluster of Coastal Community Empowerment around Shipbuilding, Cluster of Ship Repair and Maintenance. Results of KKN-PPM students carry out major programs related to the theme of the traditional shipyards and other ancillary programs that have been successfully implemented and exhibited in the â€œExpo KKN-PPMâ€ in North Karangasem, Batang district .